A Strategies To Improve Early Children's Learning Of Musical Instruments In Preschools : Strategi Meningkatkan Pembelajaran Alat Musik Anak Usia Dini Di Paud - Nisa, Khairatun (Outline Publisher, 2025)
Learning musical instruments for early childhood in PAUD often faces various challenges, such as lack of teacher skills, limited musical instruments, and lack of interest and attention of children. This research aims to identify and develop effective strategies in improving musical instrument learning for young children in PAUD. The method used in this research is a qualitative approach using observation, interview and documentation study techniques. The research subjects were teachers and students in several PAUDs in certain areas. The research results show that effective strategies involve increasing teacher competence through intensive training, providing varied and interesting musical instruments, as well as interactive and fun learning approaches. The discussion underscored the importance of collaboration between teachers, parents and the school in creating a conducive learning environment for children. The conclusion of this research is that implementing a comprehensive and sustainable strategy can significantly improve the quality of musical instrument learning in early childhood at PAUD, which in turn can support children's holistic cognitive, motoric and emotional development.